The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1085/jgp.62.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Anion Conductance of Frog Muscle Membranes: One Channel, Two Kinds of pH Dependence

Abstract: Anion conductance and permeability sequences were obtained for frog skeletal muscle membranes from the changes in characteristic resistance and transmembrane potential after the replacement of one anion by another in the bathing solution. Permeability and conductance sequences are the same. The conductance sequence at pH = 7.4 is C1-> Br-> NO > I-> trichloroacetate > benzoate > valerate >butyrate > proprionate > formate > acetate > lactate > benzenesulfonate > isethionate > methylsulfonate > glutamate > cystea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
3

Year Published

1975
1975
1996
1996

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 25 publications
9
46
3
Order By: Relevance
“…The muscle lactate concentration linearly related to that in the bath, with a ratio of distribution between muscle water and medium of about 0 3. If these results indicate that the lactate distribution between fibre water and external fluid was also nearly independent of external concentration, they are in agreement with the data of (Woodbury & Miles, 1973); it seems reasonable to assume that the mammalian fibre membrane is also permeable to lactate. On the basis of the observations reported here, exclusive permeation of lactate ions was ruled out in favour of one of lactic acid molecules.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The muscle lactate concentration linearly related to that in the bath, with a ratio of distribution between muscle water and medium of about 0 3. If these results indicate that the lactate distribution between fibre water and external fluid was also nearly independent of external concentration, they are in agreement with the data of (Woodbury & Miles, 1973); it seems reasonable to assume that the mammalian fibre membrane is also permeable to lactate. On the basis of the observations reported here, exclusive permeation of lactate ions was ruled out in favour of one of lactic acid molecules.…”
Section: Resultssupporting
confidence: 87%
“…Strictly, steady state will not be reached until EH = V. The increase in pHi without lactate, at high K, as compared to normal K (first line, Table 7) might well have been due to efflux of CO. combined with influx of bicarbonate, a mechanism entirely comparable to the lactic acid-lactate exchange. Woodbury & Miles (1973) showed that the ions of several weak acids with pKs of 4-87 or less are able to penetrate the membrane; their protonated forms are undoubtedly also permeable. Eqn.…”
Section: Resultsmentioning
confidence: 99%
“…The anion permeability and conductance sequences in these muscle fibers at pH 3.9 were found to be approximately the reverse of one another . Anion permeability and conductance sequences are essentially identical in frog skeletal muscle at pH 7.7 (Woodbury and Miles, 1973) and chloride conductance is increased at high pH (Hutter and Warner, 1967). Current-voltage relations during anion substitution (pH 7.6) in the present study showed no definitive conductance sequence.…”
Section: Discussioncontrasting
confidence: 68%
“…n = 4). This is about 3 times the value for the conductance ratio found in frog muscle, where there is known to be little interference between propionate and chloride (Woodbury & Miles, 1973). Combining this ratio with Dipolo's (1972) value for PC1 in barnacle muscle (1.9 x 10-6 cm/sec; no surface area correction), which is similar to PC, in crab muscle (A. P. Sharp, unpublished observations), gives a minimum value for the propionate anion permeability of approximately 6 x 10-8 cm/sec.…”
Section: Resultsmentioning
confidence: 55%
“…Such changes in intracellular pH (pHi) have been thought to account for some of the effects observed when the anions of weak acids are used to replace chloride (Woodbury & Miles, 1973;Kenyon & Gibbons, 1977;Marrannes & De Hemptinne, 1978). More recently, experiments in mammalian skeletal and cardiac muscle, using pH sensitive micro-electrodes, have shown pHi changes with the anions 72 A. P. SHARP AND R. C. THOMAS metabolic product) and salicylate (among other things, known to alter surface charge properties) which we considered interesting in their own right.…”
Section: Introductionmentioning
confidence: 99%